PENINGKATAN PROSES DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN METODE COURSE REVIEW HORAY (CRH) DI KELAS IV SD N 65/II SUNGAI BANGSAT KECAMATAN PELEPAT - Dahry, Sundahry; Avana, Nurlev; A, Aprizan; J, Jumiyatun (Information Technology Education Department, 2020)
This research is motivated by the low learning outcomes of mathematics in class IV. SD N 65 / II river bastard. The purpose of this research is to describe the improvement of mathematics learning processes and outcomes using the method Course Review Horay (CRH) in class IV. SD N 65 / II river bangsat pelepat sub-district”. This research is a type of classroom action research conducted with two cycles, each cycle consisting of two meetings. each cycle consists of planning,implementing, observing, and reflecting. The results of data analysis show that the use of the method Course Review Horay (CRH) can improve the process and learning outcomes of mathematics class students class IV. SD N 65 / II river bangsat. details of the results of teacher observations in the first cycle with an average teacher activity of 96.99%. In the second cycle the average teacher activity was the same at 96.99% with a very good category. The results of observations of students in the first cycle data analysis of student activity of students amounted to 62.94% with good criteria, increased to 86.35% in the second cycle with very good criteria. In the first cycle obtained an average value of student learning outcomes of 83.63% increased to 96.36% in the second cycle. while the classical completeness in the first cycle of 86.36% increased to 95.45% in the second cycle. It was concluded that the use of the method Course Review Horay (CRH) can improve the process and learning outcomes of mathematics.